The impact of corporate culture of dignity on cognitive biases, strategic decision-making and technical debt management in IT engineering - Korobkina, Tetiana; Dashenkova, Natalia; Danchenko, Iryna; Omelchenko, Halyna (Technology audit and production reserves, 2025)
The object of research is the corporate culture of dignity as an interdisciplinary determinant of organizational behavior that operates at the intersection of IT engineering, cognitive science, behavioral economics and knowledge management. The analytical focus is on the impact of cultural variables on cognitive distortions in strategic decision-making, as well as on the dynamics of technical and social debt in IT companies. The problem to be solved is the absence of a holistic cognitive-behavioral model that would describe the mechanisms of the transformative impact of a culture of dignity on organizational biases and structural inefficiencies in engineering systems. Existing approaches largely ignore the relationship between managerial ethics, team interaction architecture, and the cognitive ecology of decision-making. The research methodology included a critical analysis of theoretical sources, the development of the author’s analytical model, and a content analysis of cases of three global technology companies (Spotify, Google, Airbnb). A qualitative analysis of corporate practices and the content of open reports revealed a strong correlation between a high level of transparency, autonomy, psychological safety and feedback in organizations with a strong culture of dignity and a reduction in the frequency of cognitive distortions and the pace of technical debt elimination. The data are the result of analytical generalization rather than empirical quantitative research. Estimates show that such organizations demonstrate an acceleration in the pace of technical debt reduction by 15–20% compared to those without established feedback practices. The practical significance of research lies in the possibility of using the results to develop organizational development policies, training programmes for IT team leaders, strategic management systems and technical debt audits. The findings contribute to the expansion of theoretical understanding of the role of humanistic factors in high-tech management and have the potential to implement the UN Sustainable Development Goals, in particular in terms of decent work, inclusive governance and innovation sustainability.